Pedagogical Philosophies of Teacher Educators in the Philippines: Implications for Teacher Quality - Muthoifin Muthoifin; Mariam Elbann; Amirkhon Yorov (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2026)
This study aimed to examine the pedagogical philosophies of teacher educators in the Ilocos Region, Philippines, to understand their implications for teacher quality amid national reforms. The research sought to identify espoused philosophies, categorize them into distinct profiles, and analyze their variation across educator and institutional characteristics. A convergent parallel mixed-methods design was employed to analyze survey data from 391 teacher educators. Thematic analysis of open-ended responses was combined with quantitative profiling and cross-tabulations to map the pedagogical landscape. The results revealed a dominant model of